PENGARUH KONFLIK, LINGKUNGAN KERJA, DAN KOMUNIKASI TERHADAP KINERJA PEGAWAI PADA DINAS PENDIDIKAN DAERAH PROVINSI SULAWESI UTARA - Christisia Aprilia Valensia Lumintang; Rita N. Taroreh; Merinda H.Ch. Pandowo (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2023)
Employee performance is a result achieved by employees in their work according to applicable criteria. Good employee performance is one of the most important factors in the efforts of an organization. Good communication will improve employee performance individually and collectively.With effective communication between employees, it will make employees comfortable at work so as to reduce conflict among employees. A good work environment will contribute to employee performance at work. The purpose of this study is to determine the influence of conflict, environment, and communication toward toward employee performance at Office Education Regional of North Sulawesi Provincial. The populations in this study were all ASN/PNS employee at Office Education Regional of North Sulawesi Provincial, totaling 130 people. The sample in this study uses the Slovin formula to determine the numbers of sample are 57 respondents. The research method using multiple linear regression analysis. The analysis used included the research instrument test (validity and reliability test), multiple linear regression analysis, classic assumption test (multicollinearity test, heteroscedasticity test and normality test) and hypothesis testing (t test, F test and coefficient of determination). With this test, it can be seen how the independent variables influence the dependent variable. The results of this study found that the conflict had influence on employee performance, environment had influence on employee performance, and communication had influence on employee performance, conflict, environment, and communication simultaneously influence employee performance toward Office Education Regional of North Sulawesi Provincial.    Kata Kunci: konflik, lingkungan kerja, komunikasi, kinerja pegawai